Application of FTIR Spectroscopy method for The Quantification of Ascorbic Acid in Bulk Materials and Pharmaceutical Formulation - Alhajjeh, Rihab; Haifaa Al-Ali (Iraqi Journal of Pharmaceutical Sciences, 2024)
The present study illustrates the potential using of Fourier Transform Infrared Spectroscopy (FT-IR) in pharmaceutical analysis. A simple, rapid, non-destructive, and green (FT-IR) spectroscopy method for quality control evaluation of Ascorbic acid was developed, using potassium bromide (KBr) as a matrix to quantify the drug in bulk pharmaceutical materials and AUC its dosage forms. The sample preparation was done by mixing and grinding for disk composition and without using organic solvents. Absorbance obtained for the carbon-carbon band (C=C) located at the range (1600-1700) cm-1 was used to develop a calibration curve based on the AUC measurements. Method had been validated according to the International Conference on Harmonization (ICH) guidelines. Linearity, accuracy, precision, robustness, LOD and LOQ were evaluated and showed acceptable results for method validation in the concentration range of (2 - 12.5 mg). The validated method was able to apply for the quality control analysis of Ascorbic Acid raw materials and pharmaceutical dosage forms.